Preparation of alkali-free liquid accelerator based on aluminum sulfate and its accelerating mechanism on the hydration of cement pastes. (30th August 2020) - Niu, Mengdie; Li, Guoxin; Zhang, Jiangbo; Cao, Li
Highlights: F-AS-AF accelerator was prepared at simple and mild condition. F-AS-AF accelerator showed an excellent performance. F-AS-AF accelerator promoted the formation of ettringite and the hydration of C3 S. Abstract: The alkali-free liquid accelerator based on aluminum sulfate (F-AS-AF accelerator) was prepared and its effects on the setting time and compressive strength of cement, C3 A and C3 S were studied. The accelerator mechanism was investigated via XRD and TG. Results showed that the F-AS-AF accelerator shortened the setting time, and enhanced the early and later compressive strength of cement. With the addition of F-AS-AF accelerator, Al 3+ reacted with Ca 2+ and SO4 2− in the C3 A to rapidly form ettringite, and the consumption of Ca 2+ further promoted the dissolving and hydration of C3 S.